2004
DOI: 10.1139/v03-181
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the oxidation ofL-α-amino-n-butyric acid in moderately concentrated sulfuric acid medium

Abstract: The reaction kinetics of L-α-amino-n-butyric acid oxidation by permanganate ion have been investigated in moderately strong acid medium using a spectrophotometric technique. In all cases studied an autocatalytic effect, due to Mn+2 ions formed as a reaction product, was observed. Both catalytic and noncatalytic processes were determined to be first order with respect to the permanganate ion and the amino acid. The overall rate equation for this process may be written as: [Formula: see text] where k′1 and k′2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 15 publications
6
27
1
Order By: Relevance
“…Same trends for L-iso-leucine and L-tert-leucine similar to L-norleucine have been observed, so it could be concluded that Mn 2+ is the autocatalytic agent. But in contrast to our previous studies [15,16], for Mn 2+ to show "delayed autocatalytic characteristic," it should acquire a certain concentration, which we call "critical concentration." This critical concentration depends on the nature of amino acid used.…”
Section: Rate Equationcontrasting
confidence: 89%
See 3 more Smart Citations
“…Same trends for L-iso-leucine and L-tert-leucine similar to L-norleucine have been observed, so it could be concluded that Mn 2+ is the autocatalytic agent. But in contrast to our previous studies [15,16], for Mn 2+ to show "delayed autocatalytic characteristic," it should acquire a certain concentration, which we call "critical concentration." This critical concentration depends on the nature of amino acid used.…”
Section: Rate Equationcontrasting
confidence: 89%
“…In our previous studies [15,16], we have reported the presence of an autocatalytic effect in which Mn 2+ is an autocatalytic agent. In the present investigation, we have examined oxidation of L-norleucine, L-leucine, L-iso-leucine, and L-tert-leucine in strong acid medium by permanganate.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Deamination and decarboxylation in the chromium(III)-catalysed oxidation of L-valine by alkaline permanganate and analysis of chromium(III) in microscopic amounts by a kinetic method was studied by Kulkarni and coworkers [10] .Kinetic and mechanistic studies of oxidation of glycine and valine by Nbromosuccinimide using chloro complex of Rh(III) in its nano-concentration range as homogeneous catalyst investigated by Singh et al [11] .Kinetics and mechanisms of the permanganate oxidation of L-valine in neutral aqueous solutions was studied by Perez-benito et al [12] . Bahrami [13] had investigated kinetics and mechanism of the oxidation of L-amino-n-butyric acid in moderately concentrated sulfuric acid medium.Studies in the kinetics of oxidation of some amino acids like glycine, alanine, phenylalanine, serine, threonine, aspartic and glutamic acid by KMnO 4 in a moderately concentrated H 2 SO 4 medium in the presence and absence of Ag + has been carried out by number of workers [14][15] . Literature survey reveals that permanganate ions are widely used as oxidizing agent in synthetic and analytical chemistry [16][17] .It has several advantages as an analytical reagent.It is strong and vividly coloured.In acidic medium it exists in different forms as HMnO 4 , HMnO 4 + , HMnO 3 , Mn 2 O 7 and one depending on the nature of the reductant [18] .Glycine being a simplest amino acids and mild reductant requires powerful oxidants for studying its kinetic behavior [19] due to this permanganate is assigned as oxidant in the present investigation.…”
Section: Introductionmentioning
confidence: 99%